Seed Priming with the Selenium Nanoparticles Maintains the Redox Status in the Water Stressed Tomato Plants by Modulating the Antioxidant Defense Enzymes - Muhammad Ishtiaq; Muhammad Waqas Mazhar; Mehwish Maqbool; Tanveer Hussain; Syed Atiq Hussain; Ryan Casini; Ahmed M. Abd-ElGawad; Hosam O. Elansary (Plants, 2023)
In the present research, selenium nanoparticles (SeNPs) were tested for their use as seed priming agents under field trials on tomatoes (Solanum lycopersicum L.) for their efficacy in conferring drought tolerance. Four different seed priming regimes of SeNPs were created, comprising 25, 50, 75, and 100 ppm, along with a control treatment of 0 ppm. Seeds were planted in split plots under two irrigation regimes comprising water and water stress. The results suggest that seed priming with SeNPs can improve tomato crop performance under drought stress. Plants grown with 75 ppm SeNPs-primed seeds had lower hydrogen peroxide (H2O2) and malondialdehyde (MDA) levels by 39.3% and 28.9%, respectively. Seed priming with 75 ppm SeNPs further increased the superoxide dismutase (SOD) and catalase (CAT) functions by 34.9 and 25.4%, respectively. The same treatment increased the total carotenoids content by 13.5%, α-tocopherols content by 22.8%, total flavonoids content by 25.2%, total anthocyanins content by 19.6%, ascorbic acid content by 26.4%, reduced glutathione (GSH) content by 14.8%, and oxidized glutathione (GSSG) content by 13.12%. Furthermore, seed priming with SeNPs upregulated the functions of enzymes of ascorbate glutathione cycle. Seed priming with SeNPs is a smart application to sustain tomato production in arid lands.